Assessing the cost‐effectiveness of sodium–glucose cotransporter‐2 inhibitors in type 2 diabetes mellitus: A comprehensive economic evaluation using clinical trial and real‐world evidence. Issue 12 (2nd September 2020) - McEwan, Phil; Bennett, Hayley; Khunti, Kamlesh; Wilding, John; Edmonds, Christopher; Thuresson, Marcus; Wittbrodt, Eric; Fenici, Peter; Kosiborod, Mikhail
Abstract: Aims: The economic burden of diabetes is driven by the management of vascular complications. Sodium–glucose cotransporter‐2 inhibitors (SGLT2i) have demonstrated reductions in cardiovascular and renal complications, including hospitalization for heart failure (HHF) and renal disease progression, in randomized clinical trials. The objective of this study was to evaluate the cost‐effectiveness of the SGLT2i class versus standard of care in type 2 diabetes mellitus (T2DM), using evidence from both clinical trial and real‐world studies. Methods: An established T2DM model was adapted to use contemporary outcomes evidence from real‐world studies and randomized controlled trial evaluations of SGLT2i, and extrapolated over a lifetime for HHF, myocardial infarction, stroke, end‐stage renal disease and all‐cause mortality. The economic analysis considered adults with T2DM, with and without established cardiovascular disease, and was conducted over a lifetime from the perspective of the health care payer in the United Kingdom, United States and China, discounted at country‐specific rates. Results: SGLT2i were consistently associated with increased treatment costs, reduced complication costs and gains in quality‐adjusted life years driven by differences in projected life expectancy, cardiovascular and microvascular morbidity and weight loss. SGLT2i were estimated to be cost‐saving or cost‐effective at relevant thresholds for the overall population in the United Kingdom, United States and China, with cost‐effectiveness being the greatest in higher risk subgroups. Conclusions: The findings highlight the need to take into account cost savings from reducing common, morbid and preventable T2DM complications when considering the cost of diabetes medications.